Investigating the importance of B cells and antibodies during Trichuris muris infection using the IgMi mouse - Rinal Sahputra; Emma A Murphy; Ruth Forman; Iris Mair; Muhammad Z. H. Fadlullah; Ari Waisman; Werner Muller; Kathryn J. Else (Journal of Molecular Medicine, 2020)
The IgMi mouse has normal B cell development; its B cells express an IgM B cell receptor but cannot class switch or secrete antibody. Thus, the IgMi mouse offers a model system by which to dissect out antibody-dependent and antibody-independent B cell function. Here, we provide the first detailed characterisation of the IgMi mouse post- Trichuris muris ( T. muris ) infection, describing expulsion phenotype, cytokine production, gut pathology and changes in T regulatory cells, T follicular helper cells and germinal centre B cells, in addition to RNA sequencing (RNA seq) analyses of wild-type littermates (WT) and mutant B cells prior to and post infection. IgMi mice were susceptible to a high-dose infection, with reduced Th2 cytokines and elevated B cell-derived IL-10 in mesenteric lymph nodes (MLN) compared to controls. A low-dose infection regime revealed IgMi mice to have significantly more apoptotic cells in the gut compared to WT mice, but no change in intestinal inflammation. IL-10 levels were again elevated. Collectively, this study showcases the potential of the IgMi mouse as a tool for understanding B cell biology and suggests that the B cell plays both antibody-dependent and antibody-independent roles post high- and low-dose T. muris infection. Key messages During a high-dose T. muris infection, B cells are important in maintaining the Th1/Th2 balance in the MLN through an antibody-independent mechanism. High levels of IL-10 in the MLN early post-infection, and the presence of IL-10-producing B cells, correlates with susceptibility to T. muris infection. B cells maintain gut homeostasis during chronic T. muris infection via an antibody-dependent mechanism.